The Relationship of Personal Hygiene Knowledge with Leucorrhoea Event in Santriwati in Babus Salam Pabuaran Sibang Islamic Boarding School - Kartini Kartini; Listia Dwiwardini; Lilis Komariah (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
Reproductive health in adolescent girls is an important health problem because Indonesia is a tropical region that increases the risk of vaginal discharge due to high humidity in genetal areas and behaviors that are not optimal hygiene. The purpose of this study is to determine the relationship of personal hygiene knowledge with the incidence of fluor albus santriwati in Islamic Boarding School Babus Salam Pabuaran Sibang. Design type is quantitative research with cross sectional research method. The population in this study is santriwati class IX in Islamic Boarding School Babus Salam Pabuaran Sibang with sample of 83 respondents according to using sampling technique of consecutive sampling. Instruments used questionnaire. The majority had a high knowledge level of 63.9% and the majority of the respondents did not experience whiteness as much as 79.5%. There is p value = 0,002 (p value <α 0,05). Obtained shows the relationship between personal hygiene knowledge with the incidence of fluor albus in Islamic Boarding School Babus Salam Pabuaran Sibang. Advice for santriwati to pay more attention to personal hygiene is good to prevent the occurrence of vaginal discharge. Keywords:  Teenager; Knowledge; Personal Hygiene; Fluor Albus.